2018
DOI: 10.1111/dar.12882
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of reagent test‐kit use and perceptions of purity among ecstasy users in an electronic dance music scene in New York City

Abstract: Introduction and Aims: Ecstasy users in the electronic dance music scene are at high risk for using ecstasy adulterated with new psychoactive substances and/or methamphetamine. We examined self-reported testing of ecstasy among users in this scene. Design and Methods: We surveyed individuals (aged 18–40 years) entering electronic dance music parties in New York City in 2017. Past-year ecstasy users (n=351) were asked if they had tested their ecstasy in the past year. We estimated prevalence and correlates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…However, it is possible that some participants simply denied known use on the survey. Most recent research on adulteration or drugs such as ecstasy has focused on NPS; however, historically, ecstasy has in fact been somewhat commonly adulterated with drugs such as ketamine and cocaine 13,22,23 . Research is clearly needed to determine the source(s) of unintentional exposure to these more common drugs and research is also needed to determine whether some of this discrepant reporting is due to intentional underreporting of use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that some participants simply denied known use on the survey. Most recent research on adulteration or drugs such as ecstasy has focused on NPS; however, historically, ecstasy has in fact been somewhat commonly adulterated with drugs such as ketamine and cocaine 13,22,23 . Research is clearly needed to determine the source(s) of unintentional exposure to these more common drugs and research is also needed to determine whether some of this discrepant reporting is due to intentional underreporting of use.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reporting past‐year ecstasy use were also asked if they had found out or suspected their ecstasy being adulterated, and if so with what drug(s). These type‐in responses of drug names were double coded to ensure accuracy 13 …”
Section: Methodsmentioning
confidence: 99%
“…Results of this study suggest a strong relationship between Lean use and nonmedical use of other prescription opioids, but more research is needed to further examine this association to better inform prevention and treatment efforts. EDM party attendees appear to be increasingly aware about the dangers of drugs such as ecstasy being adulterated with other drugs (hence increased interest in drug testing); however, better education about all drugs (including Lean) may be needed both in this population and in the general population. Lean has already become glamorized and somewhat integrated with popular culture (eg, it is often displayed in a “double” Styrofoam cup throughout popular culture to indicate use) .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ecstasy users employ a variety of methods to manage the risks associated with the unidentified content of their drugs (Davis & Rosenberg, 2017), including the use of 'home' drug testing technologies (Johnstone et al, 2006). Indeed, Palamar and Barratt's (2019) recent study in the USA estimated that almost a quarter (23%) of their sample who reported past-year ecstasy use also reported having their drugs tested by such kits. This indicates that a significant body of ecstasy users undertake (what is referred to throughout this article as) independent drug checking (IDC), a process we define as the use of privately owned drug testing technologies to identify the content of illegal substances, outside of any such official services.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that home testing kits are used globally to facilitate IDC (Davis & Rosenberg, 2017;Day et al, 2018;Johnston et al, 2006;Palamar & Barratt, 2019) with sales reportedly seeing an exponential increase (Bright, 2019). However, existing knowledge around IDC is limited with extant studies focusing almost exclusively on the accuracy and harm-reduction related inferences of drug testing technologies and post drug checking drug user behaviour.…”
Section: Introductionmentioning
confidence: 99%